PERENCANAAN DAN PERANCANGAN SISTEM INORMASI MANAJEMEN PENDIDIKAN - Rosidi, Moh (Lembaga Penelitian dan Studi kebijakan MADANI Instutute, 2025)
Planning and designing an educational management information system (SIM) is a critical foundation in building an effective and efficient system in an academic environment. The first step that determines the success of this system lies in the ability to identify goals and objectives in a clear and measurable manner. Poorly defined objectives will result in a system that is irrelevant to the needs of the institution. Therefore, this identification process becomes a strategic point and guides technical, organizational aspects as well as support for managerial and operational decisions. The process of identifying SIM objectives requires the involvement of all stakeholders, ranging from institutional leaders, lecturers, administrative staff, to students. Top-down and bottom-up identification will result in a system that not only fits the organizational structure, but is also adaptive to policy changes and technological developments